WAJIB DAFTAR JAMINAN FIDUSIA DALAM PEMBIAYAAN MUDHARABAH Efektivitas Pelaksanaan Pasal 11 Undang-Undang RI Nomor 42 Tahun 1999 Tentang Jaminan Fidusia di BMT Kota Pekalongan - Triana Sofiani (JURNAL PENELITIAN, 2015)
This study aims to analyze the effectiveness of the implementation of compulsory registration of fiduciary security as stipulated in Article 11 of Law No. 42 of 1999 concerning Fiduciary Security in mudharabah financing at Baitul Maal wat Tamwil (BMT) Pekalongan, as well as the legal implications when fiduciary security is not registered at the Fiduciary Registration Office. Interviews and literature studies were used to collect data, while data triangulation was applied to ensure credibility, and the Interactive Model was used to analyze the data. The results show that the fiduciary registration requirement as stipulated in Article 11 paragraph (1) of the Fiduciary Security Law has not been effectively implemented because: (1) substantively, the article is not yet fully understood by all parties affected by the regulation; (2) law enforcement officials have not provided optimal services; (3) the legal infrastructure and facilities available do not yet provide sufficient ease and accessibility to implement the regulation; and (4) there is a lack of legal awareness among BMT managers. Legal consequences arise if fiduciary security is not registered at the Fiduciary Registration Office, namely: (1) the non-fulfillment of the principles of specialty and publicity; (2) the absence of preferential rights (the right of precedence) in debt repayment if the debtor defaults; and (3) the lack of executorial power.